Spectrum of Intracerebral Hemorrhage in Children: A Report from PICU of a Resource Limited Country. (3rd January 2016) - Abbas, Qalab; Merchant, Qurat ul Ain; Nasir, Bushra; Haque, Anwar ul; Salam, Basit; Javed, Gohar
Abstract : Intracerebral hemorrhage (ICH) in children is a rare but disabling disease that accounts for almost half cases of stroke. We report our experience of ICH in children. Retrospective review of medical records of children (1 month-16 years) admitted in Pediatric Intensive Care Unit between January 2007 and December 2014 was done. Data collected included age, gender, presentation, examination findings, neuroimaging done (CT, MRI, and angiography) management (conservative/intervention), and outcome. Results are presented as frequency and percentages. Of the total 50 patients, 58% were male and 26% were <1 year. On presentation 44% had vomiting, 42% had seizures, and GCS < 8 while 40% had altered level of consciousness. Single bleed was present in 88%, 94% had supratentorial bleed, and 32% had intraventricular extension. 72% had bleed volume of <30 mL and 8% had >60 mL. CT scan was done in 98% patients and MRI in 34%, while 6% underwent conventional angiography. 60% patients were managed conservatively, 36% underwent neurosurgical intervention, and 6% underwent radiological vascular intervention. Hematologic causes were identified in 52% patients and vascular malformations in 14% and in 26% no cause could be identified. 26% of patients expired.